To find the third, fourth, and eleventh terms of the sequence defined by the rule \( A(n) = -9 + (n-1)(6) \), we can substitute \( n \) with the appropriate values.
Finding \( A(3) \):
\[ A(3) = -9 + (3-1)(6) \] \[ A(3) = -9 + (2)(6) \] \[ A(3) = -9 + 12 \] \[ A(3) = 3 \]
Finding \( A(4) \):
\[ A(4) = -9 + (4-1)(6) \] \[ A(4) = -9 + (3)(6) \] \[ A(4) = -9 + 18 \] \[ A(4) = 9 \]
Finding \( A(11) \):
\[ A(11) = -9 + (11-1)(6) \] \[ A(11) = -9 + (10)(6) \] \[ A(11) = -9 + 60 \] \[ A(11) = 51 \]
Summary of the Terms:
- \( A(3) = 3 \)
- \( A(4) = 9 \)
- \( A(11) = 51 \)
Thus, the third term is \( 3 \), the fourth term is \( 9 \), and the eleventh term is \( 51 \).